Roles of the Pumilio domain protein PUF3 in Trypanosoma brucei growth and differentiation - Marucha, Kevin; Clayton, Christine (Parasitology, 2020)
Trypanosomes strongly rely on post-transcriptional mechanisms to control gene expression. Several Opisthokont Pumilio domain proteins are known to suppress expression when bound to mRNAs. The Trypanosoma brucei Pumilio domain protein PUF3 is a cytosolic mRNA-binding protein that suppresses expression when tethered to a reporter mRNA. RNA-binding studies showed that PUF3 preferentially binds to mRNAs with a classical Pumilio-domain recognition motif, UGUA[U/C]AUU. RNA-interference-mediated reduction of PUF3 in bloodstream forms caused a minor growth defect, but the transcriptome was not affected. Depletion of PUF3 also slightly delayed differentiation to the procyclic form. However, both PUF3 genes could be deleted in cultured bloodstream- and procyclic-form trypanosomes. Procyclic forms without PUF3 also grew somewhat slower than wild-type, but ectopic expression of C-terminally tagged PUF3 impaired their viability. PUF3 was not required for RBP10-induced differentiation of procyclic forms to bloodstream forms. Mass spectrometry revealed no PUF3 binding partners that might explain its suppressive activity. We conclude that PUF3 may have a role in fine-tuning gene expression. Since PUF3 is conserved in all Kinetoplastids, including those that do not infect vertebrates, we suggest that it might confer advantages within the invertebrate host.